Silica Fume and Aluminum Powder Effects on Strength and Porosity of Pervious Concrete under Peat and PDAM Curing - Hariyani, Susi; Nizar, Nizar; Justitiannisa, Innino (Jurnal Teknik Sipil, 2026)
Pervious concrete used in peatland environments is susceptible to durability loss due to acidic, organic-rich exposure that alters its pore structure and matrix integrity. This study evaluates the effects of silica fume (SF) and aluminum powder (AP) on the compressive strength and porosity of pervious concrete under two curing media: PDAM water and peat water. SF contents ranging from 0–10% and AP contents from 0–0.9% by cement weight were investigated. Compressive strength and porosity tests were conducted at 28 and 56 days to assess mechanical and physical performance, whereas durability trends were interpreted through microstructural considerations. The results indicate that PDAM water curing yields higher strength and lower porosity compared with peat water curing. SF incorporation enhances matrix densification through pozzolanic reactions, reducing pore connectivity, whereas appropriate AP dosages help stabilize the internal pore network. The optimal mixture achieved a compressive strength of 50.88 kg/cm² and porosity of 16.98%. Even under aggressive peat-water curing, modified mixtures exhibited improved performance, suggesting greater durability potential.